Answer: see proofs below
Explanation:
7i) (ab + bc)(ab - bc) = a²b² - ab²c + ab²c - b²c² → a²b² - b²c²
+ (bc + ca)(bc - ca) = b²c² - abc² +abc² - a²c² → b²c² - a²c²
+ (ca + ab)(ca - ab) = a²c² - a²bc + a²bc - a²b² → a²c² - a²b²
= a²b² + 0 + 0 - a²b²
= 0
7ii) a(a² + b² + c² - ab - bc - ca) = a³ + ab² + ac² - a²b - abc - a²c
+ b(a² + b² + c² - ab - bc - ca) = b³ - ab² + bc² + a²b - abc - b²c
+ c(a² + b² + c² - ab - bc - ca) = c³ - ac² - bc² - abc + a²c + b²c
= a³ + b³ + c³ + 0 + 0 + 0 + 0 - 3abc + 0 + 0
= a³ + b³ + c³ - 3abc
7iii) p(p² + pq + q²) = p³ + p²q + pq²
-q(p² + pq + q²) = - p²q - pq² - q³
= p³ + 0 + 0 - q³
= p³ - q³